The Validity of Interactive Multimedia on Metal Coating Learning Developed Using the ADDIE Model - Erma Yulia; Selamat Riadi; Banu Nursanni (Postgraduate, University of Mataram, 2023)
The Metal Coating course in Unimed's Mechanical Engineering Education Department only uses learning media in the form of printed textbooks and there is no interactive media that can improve student competence in the affective and psychomotor domains. To increase student competency in metal plating courses, learning media in the form of interactive multimedia that has been validated for its quality is needed. This study aims to validate learning media in the form of interactive multimedia using the ADDIE development model. As for the three acquisitions of interactive multimedia validity, namely analysis of metal plating course requirements, determining learning objectives and designing interactive multimedia, as well as developing interactive multimedia involving several material experts, learning design experts, and learning media experts, as activity validators. Data collection techniques for interactive multimedia validation are carried out by distributing questionnaires. The validation assessment criteria used a Likert scale which was analyzed descriptively. The results showed that the validity of the material expert was 89.7% in the very good category, the learning design expert was 91.58% in the very good category and the learning media expert was 88.3% in the very good category. from these data it can be concluded that the use of interactive multimedia in the teaching and learning process in the metal plating course developed is very valid to be implemented in the teaching and learning process